The international economic policy of the United States : selected papers of C. Fred Bergsten, 1977-1979 - Bergsten, C. Fred (Lexington, Mass. : LexingtonBooks, 1980)
This book records US policy in the area of international economic policy between 1977 - 1979. The paper examines the energy problem that had remained unresolved, with high rising oil prices intensified both inflation and unemployment.
includes list of figures
Includes bibliographical references and index.
ijb, 14/01/2019
Loans
Keywords: Foreign economic relations; United States